Zoneamento ambiental de bacias hidrográficas: uma abordagem metodológica aplicada na bacia do Rio Bonito (SP) - Moraes, Maria Eugênia Bruck de (Universidade Federal de São Carlos, 2003)
The use of the concept for sustainable development in studies of Applied Ecology has brought a large increasein the number of analysis and environmental planning methodologies. It comes particularly into a view the development of diagnosis and prognosis evaluation related to water-basin environmental zoning. Within this context, this paper deals with the issue of environmental zoning by usisng remote sensing and geoprocess technologies. It elaborates two different zonning proposals for River Bonito Water Basin in the state of São Paulo, using both analytic and synthetic approaches. It also deals with features related to incidental environmental law in the considered area, potentialities and restrictions imposed by physical environment in regard to law use, as well as the current state of degradation of itis natural resources. Advantages and disadvantages of methodological approaches and the techniques used are also analyzed through some of methodological approaches and the techniques used are also analyzed through some maps. Finally, it presents na environmental diagnosis with important data for basin planning and management.
Keywords: Zoneamento ambiental; Política ambiental; Bacia hidrográfica; Ecologia de paisagem; Sistema de informação geográfica; Water-basin; Landscape ecology; Environmental planning; Environmental zoning; Geographic information system; CIENCIAS BIOLOGICAS::ECOLOGIA